2021
DOI: 10.1101/2021.07.26.453741
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The cryo-EM structure of the chloroplast ClpP complex reveals an interaction with the co-chaperonin complex that inhibits ClpP proteolytic activity

Abstract: Protein homeostasis in plastids is strategically regulated by the protein quality control system involving multiple chaperones and proteases, among them the Clp protease. We determined the structure of the chloroplast ClpP complex from Chlamydomonas reinhardtiiby cryo-EM. ClpP contains two heptameric catalytic rings without any symmetry. The top ring contains one ClpR6, three ClpP4 and three ClpP5 subunits while the bottom ring is composed of three ClpP1C subunits and one each of the ClpR1-4 subunits. ClpR3, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…We previously observed and highlighted a strong enrichment of CPN20 in protein interactome analysis of CLPT1,2 ( 43 ). Interesting, a recent cryo-EM structure of the affinity-purified chloroplast CLPPR protease complex from the green algae Chlamydomonas reinhardtii showed that a heterotetramer of CPN11, CPN20, and CPN23 associated with one of the axial sides of the CLP core complex to form a stable 550-kDa complex ( 48 ). It was suggested that this cochaperone complex could play a role in coordinating protein folding and degradation in the Chlamydomonas chloroplast.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously observed and highlighted a strong enrichment of CPN20 in protein interactome analysis of CLPT1,2 ( 43 ). Interesting, a recent cryo-EM structure of the affinity-purified chloroplast CLPPR protease complex from the green algae Chlamydomonas reinhardtii showed that a heterotetramer of CPN11, CPN20, and CPN23 associated with one of the axial sides of the CLP core complex to form a stable 550-kDa complex ( 48 ). It was suggested that this cochaperone complex could play a role in coordinating protein folding and degradation in the Chlamydomonas chloroplast.…”
Section: Resultsmentioning
confidence: 99%
“…Several of these proteins are direct components of the CLP chaperone-protease system (CLPF, CLPT1, CLPT2, CLPD). The >10-fold enrichment of cochaperone pair CPN10 and CPN20 is highly intriguing given the recent identification in the Chlamydomonas CLP core structure through cryo-EM ( 48 ); perhaps the CPN10/20 proteins also directly interact with the CLP protease core complex to regulate access to the catalytic chamber.…”
Section: Discussionmentioning
confidence: 99%